2013
DOI: 10.1002/jez.1844
|View full text |Cite
|
Sign up to set email alerts
|

Erythrophagocytosis in circulating blood of loggerhead turtlesCaretta caretta: The pitting of Heinz bodies

Abstract: In humans red blood cells live on average of 120 days. Senescent erythrocytes are removed from circulation by macrophages; this process, called erythrophagocytosis (EPC), takes place mainly in the liver but also in the bone marrow. We studied this process in loggerhead turtles Caretta caretta, inhabiting the Mediterranean Sea. Leukocytes of reptiles include heterophils, eosinophils, lymphocytes, basophils, thrombocytes, monocytes, and of these heterophils and monocytes represent the main phagocytic cells. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
2
4
0
1
Order By: Relevance
“…Finally, we question the interpretation of some of the cytochemical staining results of leukocytes as shown in the second paper (Fig. , Ruggiero et al, ). Heterophils appear to be negative rather than positive for peroxidase, and the CAE‐positive cell is likely an eosinophil, rather than a heterophil.…”
Section: Heinz Bodies and Erythrophagocytosis In The Peripheral Bloodmentioning
confidence: 87%
See 1 more Smart Citation
“…Finally, we question the interpretation of some of the cytochemical staining results of leukocytes as shown in the second paper (Fig. , Ruggiero et al, ). Heterophils appear to be negative rather than positive for peroxidase, and the CAE‐positive cell is likely an eosinophil, rather than a heterophil.…”
Section: Heinz Bodies and Erythrophagocytosis In The Peripheral Bloodmentioning
confidence: 87%
“…A second paper from this laboratory, Ruggiero et al () describes erythrophagocytosis by heterophils in the peripheral blood. Erythrophagocytosis is identified by intracytoplasmic whole or fragmented erythrocytes, sometimes also with variable amounts of greenish‐basophilic material suggestive of hemosiderin (Fig.…”
Section: Heinz Bodies and Erythrophagocytosis In The Peripheral Bloodmentioning
confidence: 99%
“…Figure 4 a,b by Di Santi et al are reported to show heterophils phagocytizing parasitized erythrocytes. The morphologic description of erythrophagia in loggerhead turtles has been recently addressed (Stacy and Harvey 2015) in response to another publication by this laboratory (Ruggiero et al 2013). As stated previously, we disagree that erythrophagia is present in the images in which it is described.…”
mentioning
confidence: 88%
“…The capacity of this parasite to cause host cell transformation is unique among eukaryotic pathogens. In fact, as textually reported by Marsolier et al (2015), BTheileria is the only Genus that transforms its mammalian host cells.^In addition, the detection of active erythrophagocytosis in circulating blood is another recognized phenomenon in response to parasitization (Jaensch and Raidal 2006;Ruggiero et al 2014). Moreover, Theileria-infected cells were detected and photographed in ideal areas in the center of microscopic fields and not in thick-smeared regions.…”
mentioning
confidence: 92%